Dampak Digitalisasi Rantai Pasok terhadap Efisiensi Biaya dan Daya Saing Usaha Mikro Kecil Menengah (UMKM) lokal di Era Ekonomi Digital - Yoseph Erbito; Veneranda Rini Hapsari (Politeknik Ganesha Medan, 2026)
This study aims to analyze the impact of supply chain digitalization on operational cost efficiency and competitiveness of local Micro, Small, and Medium Enterprises (MSMEs) in the digital economy era. Amidst market competition that increasingly demands speed and efficiency, local MSMEs face challenges such as logistics cost inefficiencies and weak coordination. Supply chain digitalization through the integration of information technology, such as cloud-based inventory management systems, digital procurement platforms, and data analytics, offers a solution to address these issues. The research method used is a quantitative explanatory study with a survey technique of MSME actors in the Bengkayang Regency area, West Kalimantan. Data were analyzed using multiple linear regression techniques to examine the effect of supply chain digitalization variables on cost efficiency and competitiveness. The results show that the adoption of supply chain technology contributes significantly to reducing operational costs through optimizing logistics routes, minimizing inventory waste, and accelerating response times to customer orders. In addition, supply chain digitalization has been proven to increase the competitiveness of local MSMEs through business process transparency that strengthens customer trust and more flexible adaptability to changes in market consumption patterns. This study concludes that supply chain digitalization is a crucial strategy for local MSMEs to maintain business continuity and compete in an integrated digital economy ecosystem